Meningkatkan Nilai Tambah Urin Sapi Menjadi Pupuk Organik Cair Melalui Fermentasi - Shodiq Eko Ariyanto; Nova Laili Wisuda (Muria Jurnal Layanan Masyarakat, 2019)
General Purpose of Appropriate Technology for Fermentation of Cow Urine to Liquid Organic Fertilizer is an effort to increase the added value of livestock wastewater. This activity is a downstream process of the utilization of cattle wastewater from research results to the community, can increase the productivity of added value, quality and competitiveness of technology products processing liquid livestock waste into liquid organic fertilizer based on science and technology. He methods and stages in applying technology to the people used are: the socialization of technology for processing liquid cattle manure into liquid organic fertilizer through fermentation design of cow urine processing equipment for liquid fertilizer production, assistance in the production of liquid organic fertilizer, and packaging of liquid organic fertilizer, reporting, follow-up, monitoring and evaluation. The results of the activity are liquid processing of manure, liquid organic fertilizer, and publications in the mass media and publications in ISSN journals. The liquid organic fertilizer product of this activity has a nutrient content quality above the SNI standard